Photochromic Materials: More Than Meets The Eye - Zhang, Junji; Zou, Qi; Tian, He (Advanced materials (Weinheim), 2013)
Photochromic materials are a family of compounds which can undergo reversible photo‐switches between two different states or isomers with remarkably different properties. Inspired by their smart photo‐switchable characteristics, a variety of light‐driven functional materials have been exploited, such as ultrahigh‐density optical data storage, molecular switches, logic gates, molecular wires, optic/electronic devices, sensors, bio‐imaging and so on. This review commences with a brief description of exciting progress in this field, from systems in solution to modified functional surfaces. Further development of these photo‐switchable systems into practical applications as well as existing challenges are also discussed and put in prospect. Inspired by the smart photoswitchable characteristics of photochromic materials, a variety of light‐driven functional materials have been exploited, such as ultrahigh‐density optical data storage, molecular switches, logic gates, molecular wires, optic/electronic devices, sensors, bio‐imaging and so on. This review commences with a brief description of exciting progress in this field and further development of these photo‐switchable systems into practical applications as well as existing challenges are also discussed.